Rancang Bangun Sistem Kendali Suhu dan Level Air pada Boiler di Kapal Tanker Menggunakan Outseal PLC dan HMI - Rizky Pradana Ilyas; Sonhaji Sonhaji; Henna Nurdiansari (Pusat Riset dan Inovasi Nasional, 2025)
On tanker ships, boilers play a crucial role in providing steam for various operational needs. The stability and reliability of the temperature and water level control system are essential to maintaining efficiency and safety on board. This research aims to design and develop an automatic control system using Outseal PLC and HMI to regulate the temperature and water level in boilers. The research method used is experimental, where the system is designed, developed, and tested to evaluate its effectiveness.The system design involves a DS18B20 sensor to detect temperature, an ultrasonic sensor to measure water levels, and a heater as a heating actuator. The Outseal PLC functions as the main control unit, while the HMI facilitates monitoring and operation. The results show that the system can control water temperature within the desired range, with an average setpoint achievement time of 3.5 to 4.5 minutes. Additionally, the water level control system operates in real-time with a high level of accuracy.The implementation of this automatic control system based on Outseal PLC and HMI is expected to improve operational efficiency and safety on tanker ships. Moreover, it can serve as a reference for developing similar control systems in the maritime industry.